2016
DOI: 10.1177/0040517515621135
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly salt-free reactive dyeing of cotton (muslin) fabric after cationization with amino acid from soya

Abstract: Bleached cotton fabric was chemically modified (cationized)with natural amino acids extract obtained by acid hydrolysis (6N HCL) from soya bean seed waste, adding MgCl2 as an acid donor in the pad-dry-calendaring process to investigate the changes in textile properties and its dyeability with reactive dye in both a conventional alkaline dye bath and salt-free acidic dye bath. This modified cotton incorporates new functional groups producing [Formula: see text] in acid bath to obtain cationized cotton, renderin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The results showed that salt-free and alkali-free reactive dyeing is possible in producing medium to extradark dye shades without affecting the dyeing time. Samanta et al [159] proposed a method for the eco-friendly, salt-free reactive dyeing of cotton fabric after cationisation with amino acids from soya. It was discovered from the study that cotton treated with the soya extract provided a new route for eco-friendly, salt-free reactive dyeing with high exhaustion-type reactive dyes showing much higher dye uptake than the control on the cotton fabric.…”
Section: Cotton Wet Processing and Finishingmentioning
confidence: 99%
“…The results showed that salt-free and alkali-free reactive dyeing is possible in producing medium to extradark dye shades without affecting the dyeing time. Samanta et al [159] proposed a method for the eco-friendly, salt-free reactive dyeing of cotton fabric after cationisation with amino acids from soya. It was discovered from the study that cotton treated with the soya extract provided a new route for eco-friendly, salt-free reactive dyeing with high exhaustion-type reactive dyes showing much higher dye uptake than the control on the cotton fabric.…”
Section: Cotton Wet Processing and Finishingmentioning
confidence: 99%
“…The K/S values from eight different sites on the dyed fabrics were measured using a Datacolor 650 spectrophotometer under illuminant D65 and 10 standard observer. Then 4E, namely the standard deviation of K/S value, could be calculated according to equations (7) and (8), which can be used to assess the leveling property of the dyed fabrics…”
Section: Leveling Propertymentioning
confidence: 99%
“…A number of efforts have been made to solve these issues in the context of pigments and fabric. 7 For example, the introduction of positive charges onto the fabric surface by cationic pretreatment of fabrics, then the cationic fabrics attract pigments charging negative charges. Wang et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7,[11][12][13][14][15][16][17][18][19][20][21][22] Proteins from vegetable sources such as those extracted from soybean were also investigated for the same purpose. 23,24 Ovalbumin is the main protein found in egg white; 25 its use in cotton cationization has not yet been reported for improvement in dyeing. For protein fixation in cotton, crosslinkers are generally used such as those based on methylolamide (DMDHEU and DMeDHEU) [12][13][14]19 and citric acid.…”
mentioning
confidence: 99%